ANALISIS PENGGUNAAN APLIKASI INLISLITE DALAM PENGELOLAAN KOLEKSI BAHAN PUSTAKA DI DINAS PERPUSTAKAAN DAERAH SUMATERA SELATAN - Kartika Sari; Mulyadi; Asmawati (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2023)
The National Library of Indonesia (Perpusnas) has been creating and developing the software and library automation program Inlislite since 2011. This study attempts to ascertain how librarians use the Inlislite system in the province of South Sumatra, as well as the challenges they face and the efforts they make. This study employed a descriptive qualitative methodology. The steps of observation, interviews, and documentation were used to gather data. According to the study's findings, Inlislite has been used extremely successfully for the collection material management system at the South Sumatra library service. Utilization of Inlislite (Integrated Library System), which comprises management of library resources, circulation services (borrowing and returning books), membership, and OPAC. Inlislite is used with version 3.2. stumbling blocks in employing Inlislite The National Library of Indonesia (Perpusnas) has been creating and developing the software and library automation program Inlislite since 2011. This study attempts to ascertain how librarians use the Inlislite system in the province of South Sumatra, as well as the challenges they face and the efforts they make. This study employed a descriptive qualitative methodology. The steps of observation, interviews, and documentation were used to gather data. According to the study's findings, Inlislite has been used extremely successfully for the collection material management system at the South Sumatra library service. Utilization of Inlislite (Integrated Library System), which comprises management of library resources, circulation services (borrowing and returning books), membership, and OPAC. Inlislite is used with version 3.2. stumbling blocks in employing Inlislite